Reconstruction of images with RPCA and augmenting 3D model - Tahiti, Tasnia Jasim; Yusuf, Talha; Shakhawat, Chowdhury Abrar (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.